2018
DOI: 10.1371/journal.pone.0195080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the natural arsenic gradient on the diversity and arsenic resistance of bacterial communities of the sediments of Camarones River (Atacama Desert, Chile)

Abstract: Arsenic (As), a highly toxic metalloid, naturally present in Camarones River (Atacama Desert, Chile) is a great health concern for the local population and authorities. In this study, the taxonomic and functional characterization of bacterial communities associated to metal-rich sediments from three sites of the river (sites M1, M2 and M3), showing different arsenic concentrations, were evaluated using a combination of approaches. Diversity of bacterial communities was evaluated by Illumina sequencing. Strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 69 publications
2
6
1
1
Order By: Relevance
“…Significant differences in arsenic concentrations were observed in each site As1 (dry 120 µg g -1 ; wet 103 µg g -1 ), As4 (dry 590 µg g -1 ; wet 521 µg g -1 ), As7 (dry 964 µg g -1 ; wet 1310 µg g -1 ), As9 (dry 992 µg g -1 ; wet 1700 µg g -1 ); As12 (dry 564 µg g -1 ; wet 675 µg g -1 ). Concentrations of arsenic in samples As7 and As9 were the highest, and are comparable to those in other mining-affected river sediments (Azcue et al 1994, Leon et al 2018. Wet season arsenic concentrations in samples As7, As9 and As12 were higher than their respective dry season concentrations.…”
Section: Geochemical and Mineralogical Characteristics Of Sedimentssupporting
confidence: 68%
“…Significant differences in arsenic concentrations were observed in each site As1 (dry 120 µg g -1 ; wet 103 µg g -1 ), As4 (dry 590 µg g -1 ; wet 521 µg g -1 ), As7 (dry 964 µg g -1 ; wet 1310 µg g -1 ), As9 (dry 992 µg g -1 ; wet 1700 µg g -1 ); As12 (dry 564 µg g -1 ; wet 675 µg g -1 ). Concentrations of arsenic in samples As7 and As9 were the highest, and are comparable to those in other mining-affected river sediments (Azcue et al 1994, Leon et al 2018. Wet season arsenic concentrations in samples As7, As9 and As12 were higher than their respective dry season concentrations.…”
Section: Geochemical and Mineralogical Characteristics Of Sedimentssupporting
confidence: 68%
“… 15 Therefore the possible occurrence of resistance genes related to arsenic (As) contamination in lake microbes can be investigated with genome resolved metagenomics approach. 75 - 78 Importantly, arsenic (As) resistant and metabolism-related genes were found to be present in the recovered genome bins of the lake sample ( Figure 5 and Supplementary Table S6 ); This is an indication that the mechanism to stabilize the Arsenic toxicity is already active in the lake microbes. The predominant forms of As in environment are inorganic arsenate (As [V]) and arsenite (As [III]).…”
Section: Discussionmentioning
confidence: 96%
“…We demonstrated that the assembled bacterial and fungal genera inhabiting the root and rhizosphere compartments of P. vittata were reportedly involved in As cycling. For example, the bacterial genera Gemmatimonas, Lysobacter and Nitrospira are tolerant to high levels of As and are widely identified in As-contaminated environments, such as soil (Sun et al, 2019), rivers (Halter et al, 2011;Leon et al, 2018) and tailing dumps (Xiao et al, 2016a). Opitutus and Penicillium were identified as arsenate-reducing bacteria and are widely reported in Ascontaminated soils (Xiao et al, 2016c), activated sludge and coastal sediments (Cai et al, 2013).…”
Section: Root Microbiome Facilitates As Requisition Of P Vittatamentioning
confidence: 99%